Trends in food consumption by degree of processing and diet quality over 17 years: results from the Framingham Offspring Study. Issue 12 (28th December 2021) - Juul, Filippa; Lin, Yong; Deierlein, Andrea L.; Vaidean, Georgeta; Parekh, Niyati
Abstract: Ultraprocessed foods provide the majority of energy content in the American diet, yet little is known regarding consumption trends over time. We determined trends in diet processing level and diet quality from 1991 to 2008 within the prospective Framingham Offspring Cohort. Dietary intakes were collected by FFQ quadrennially 1991–2008 (total of four examinations). The analytical sample included 2893 adults with valid dietary data for ≥3 examinations (baseline mean age = 54 years). Based on the NOVA framework, we classified foods as: unprocessed/minimally processed foods; processed culinary ingredients (salt/sugar/fats/oils); and processed foods and ultraprocessed foods. We evaluated diet quality using the Dietary Guidelines for Americans Adherence Index (DGAI) 2010. Trends in consumption of foods within each processing level (servings/d) and diet quality over the four examinations were evaluated using mixed effects models with subject-specific random intercepts. Analyses were stratified by sex, BMI (<25 kg/m 2, 25–29·9 kg/m 2, ≥30 kg/m 2 ) and smoking status. Over 17 years of follow-up, ultraprocessed food consumption decreased from 7·5 to 6·0 servings/d and minimally processed food consumption decreased from 11·9 to 11·3 servings/d ( P trend < 0·001). Changes in intakes of processed foods, culinary ingredients and culinary preparations were minimal. Trends were similar by sex, BMI and smoking status. DGAI-2010 score increased from 60·1 to 61·5, P < 0·001. The current study uniquely describes trends in diet processing level in an ageing US population, highlighting the longstanding presence of ultraprocessed foods in the American diet. Given the poor nutritional quality of ultraprocessed foods, public health efforts should be designed to limit their consumption.